Diagnostic radiological examinations and risk of intracranial tumours in adults—findings from the Interphone Study. (14th October 2021) - Auvinen, Anssi; Cardis, Elisabeth; Blettner, Maria; Moissonnier, Monika; Sadetzki, Siegal; Giles, Graham; Johansen, Christoffer; Swerdlow, Anthony; Cook, Angus; Fleming, Sarah; Berg-Beckhoff, Gabriele; Iavarone, Ivano; et al.
Abstract: Background: Exposure to high doses of ionizing radiation is among the few well-established brain tumour risk factors. We used data from the Interphone study to evaluate the effects of exposure to low-dose radiation from diagnostic radiological examinations on glioma, meningioma and acoustic neuroma risk. Methods: Brain tumour cases (2644 gliomas, 2236 meningiomas, 1083 neuromas) diagnosed in 2000–02 were identified through hospitals in 13 countries, and 6068 controls (population-based controls in most centres) were included in the analysis. Participation across all centres was 64% for glioma cases, 78% for meningioma cases, 82% for acoustic neuroma cases and 53% for controls. Information on previous diagnostic radiological examinations was obtained by interviews, including the frequency, timing and indication for the examinations. Typical brain doses per type of examination were estimated based on the literature. Examinations within the 5 years before the index date were excluded from the dose estimation. Adjusted odds ratios were estimated using conditional logistic regression. Results: No materially or consistently increased odds ratios for glioma, meningioma or acoustic neuroma were found for any specific type of examination, including computed tomography of the head and cerebral angiography. The only indication of an elevated risk was an increasing trend in risk of meningioma with the number of isotope scans, but no such trends for other examinations were observed. No gradient was found in risk with estimated brain dose. Age at exposure did not substantially modify the findings. Sensitivity analyses gave results consistent with the main analysis. Conclusions: There was no consistent evidence for increased risks of brain tumours with X-ray examinations, although error from selection and recall bias cannot be completely excluded. A cautious interpretation is warranted for the observed association between isotope scans and meningioma.